Typological Features of the Personal Identity of Women Convicted to Deprivation of Freedom - Herasimenko, Olga Anatoliyivna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article analyzes the work of scientists who considered identity as a psychological and social phenomenon. The concept of identity as a complex integrated socio-psychological formation and as a category of adaptive resources of the individual is considered. The problem of formation of personal identity and its influence on socialization and formation of human personality is covered. The insufficiency of theoretical substantiations of studying the peculiarities of personal identity as a structural component of the personality of women sentenced to imprisonment is shown. Personal identity is considered as an important resource for resocialization of convicts. It is noted what changes the personal identity undergoes during the sentence, which is associated with changes in social roles and self-esteem, social stigma, disruption of family ties, difficulties in restoring social functioning (job search, housing, etc.). The importance of the problem of resocialization of convicts, which is due to the need to ensure an individual approach to convicts and persons released from prisons, preventing their return to a criminal lifestyle, the formation of socially favorable forms of behavior after release. The process of resocialization is considered as a complex problem determined by the social environment in which the punishment takes place, the specifics of interpersonal interactions in this environment, the psychological characteristics of the personality of convicts. The study empirically identified the typology of personal identity of women sentenced to imprisonment at the stage of their resocialization, which includes four types of women sentenced to imprisonment: passive-depressed, sociable, self-confident, infantile. The given meaningful description of the types of personal identity of women sentenced to imprisonment can be used to develop measures for their psychological support and correction.